Diversification of development and the use of the natural and cultural attractions of the Dinaric Karst - Kapusta, Armina (Turystyka w badaniach podstawowych, 2023)
The Dinaric Karst is a geographic region with significant natural value, a key factor in the development of tourism in this area. Natural conditions influence the need to adapt to local conditions, resulting in a specific way of life and land development which have become cultural values. The aim of this paper is to present the tourist attractions of the region together with a discussion of selected attractions, their development, and the possibility of making them available to tourists, while taking care to the authenticity of the natural and cultural landscape.